Knowledge, Attitude, and Practice Related to Renal Diet in Hemodialysis Patients: An Analysis of the Impact of Socioeconomic Status on KAP - Talat, Aiza; Javaid, Ribaha; Umm-e-Habiba; Kamal, Faiza; Jamshaid, Ayesha (International Health Review, 2025)
Hemodialysis patients require major modifications in their behavior and dietary pattern for catering to their health complications. Slight inaccuracies in diet and practices can create severe complications for patients including overhydration, hyperkalemia, and phosphorus excess. Patients must have adequate knowledge to maintain the optimum balance of minerals and dry weight. The objective of the study was to assess the dietary knowledge of hemodialysis patients and compare it with their attitudes and practices. Also, to examine the effect of socioeconomic status on knowledge, attitudes and practices (KAP). For this purpose, data was collected from 6 different hospitals across Lahore that include Hijaz Hospital, Jinnah Hospital, Bahria International Hospital, Indus Hospital, Services Hospital, and Skyline welfare trust. The target population included the hemodialysis patients both males and females with no specification regarding race or ethnicity. Convenience sampling was employed to gather data from available dialysis patients. The result’s analysis reported that out of 306 participants, 54.9% were male and 16.1% were female. Gender comparison demonstrated that males exhibited more favorable attitudes than females. Analysis of the KAP questionnaire revealed that 64.4% of patients had good knowledge, while 77.4% demonstrated a positive attitude. In conclusion, the study reveals that the socioeconomic status of most patients marked significant differences in their level of knowledge and attitude, however, practices remain unaffected from socioeconomic status. Education appears to have a strong correlation with good knowledge about renal diet, whereas attitudes and practices are independent of it.